2005
DOI: 10.1002/ijc.21158
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin increases invasiveness of prostate cancer cells: Role for cyclic AMP-dependent protein kinase A in calcitonin action

Abstract: Calcitonin (CT) is synthesized and secreted in prostate epithelium, and its secretion from malignant prostates is several-fold higher than from benign prostates. CT receptor (CTR) is expressed in malignant prostate epithelium, and its activation stimulates growth of prostate cancer (PC) cells via activation of adenylyl cyclase and calcium/phospholipid pathways. To identify the role of ''CT System'' in prostate cancer, we tested the expression of CT and CTR mRNAs in invading tumor cells of prostate cancer speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 56 publications
8
55
0
2
Order By: Relevance
“…The profile of these results is almost identical to that of CT-induced increase in invasion, as described previously. 23 A second major high-molecular-weight band (140 kDa) may correspond to PAI-1-uPA-uPA receptor complex as suggested by a recent report. 40 …”
Section: Cell-bound Upa In Pc-3m Cell Lysatesmentioning
confidence: 83%
See 4 more Smart Citations
“…The profile of these results is almost identical to that of CT-induced increase in invasion, as described previously. 23 A second major high-molecular-weight band (140 kDa) may correspond to PAI-1-uPA-uPA receptor complex as suggested by a recent report. 40 …”
Section: Cell-bound Upa In Pc-3m Cell Lysatesmentioning
confidence: 83%
“…The increase was at least 3-fold in response to 10 nM CT (the lowest tested concentration), and increased to 7-fold when treated with 1 lM CT (the highest tested concentration). Since our previous studies have shown that CT increases invasiveness of various PC cell lines through the activation of protein kinase A, 37 we tested a possibility that CT may stimulate uPA secretion by the same mechanism. We examined the effect of Rp.cAMP (100 lM), a membrane-permeable competitive inhibitor of cyclic AMPdependent protein kinase A, on CT-induced uPA secretion by PC-3M cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations